Spontaneous bilateral basal ganglia haemorrhage secondary to methanol poisoning - Sohor, Norainon J; Loh, Wei Chao; Pang, Rong Yao; Khan, Abdul Hanif; Chia, Peck Kee; Wan Sulaiman, Wan Aliaa; Mat, Liyana Inche; Hoo, Fan Kee; Basri, Hamidon (Medknow, 2024)
Methanol toxicity remains as major problem in the medical field.[1-3] With its active metabolite, formic acid often leads to severe metabolic acidosis and to some extend brain damaged.[4-6] We are reporting a case of brain hemorrhage at the right external capsule and left basal ganglia with mass effect and obstructive hydrocephalus in a methanol poisoning patient. A confused 29-year-old gentleman was brought into hospital. Initial investigation showed severe metabolic acidosis with raised anion gap. Initial brain CT scan was normal. Subsequently, serum methanol was reported to be high (112 mg/dL). Intravenous (IV) ethanol 10% was given without any delayed. As there was no improvement in his consciousness level, a repeat brain CT was performed and it showed multiple cerebral hemorrhage with obstructive hydrocephalus. Hence, clinicians should have high index of suspicion for cerebral hemorrhage in a patient with methanol toxicity, who presented with altered mental status and severe metabolic acidosis.